Fishery Economics and Game Theory - Lone Grønbæk (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2000)
Game theory is an analytical tool for modeling strategic interaction between agents. Strategic interaction in fishery is interpreted as the harvest by one agent highly affects other agents decision. This paper is a commented literature study on the fishery economics and game theory. It tends to describe how fishery models using game theory are build up. These models consist of an underlying biological models and the game-theoretical computational concepts. The paper then describes different types of fishery and how these types are related to game theory. Special features as externalities and irreversib le capital are discussed. The paper then presents two classic models of fishery economics using game theory. Two newer papers using game theory are discussed. Finally, the paper concludes with ideas for further research.
Keywords: 330; Fischerei; Spieltheorie; Theorie